Challenges and Strategies for Implementing Discipline Policy at Elementary School: Collaborative Analysis between Principal, Teachers, and Parents - Wantini, Wantini; Karsono, Karsono; Winarno, Winarno (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Student discipline is a crucial part in character development and academic achievement in primary education. At Elementary School 1 Kemiri Boyolali, the discipline policy, executed via the School Literacy Movement (SLM) program and the 5S culture, seeks to enhance student participation in learning. The execution of this policy encounters obstacles including insufficient resources, inadequate parental engagement, and discrepancies in teachers' methods of implementing punishment. This study seeks to examine the responsibilities of the principal, teachers, and parents in facilitating the execution of discipline rules, as well as to identify the obstacles and solutions employed inside the school. The employed methodology is qualitative, utilising a case study at Elementary School 1 Kemiri Boyolali, incorporating observational techniques and semi-structured interviews with the principal, educators, and parents. Data analysis employed a thematic approach, involving systematic coding of interview transcripts and observation notes to identify patterns related to stakeholder roles, obstacles, and solutions. The study's findings suggest that collaboration among the principal, teachers, and parents is crucial for effective punishment implementation, despite existing challenges in coordination and time limitations. This study underscores the significance of collaboration among stakeholders in fostering an effective culture of discipline in educational institutions. This study offers practical insights for primary schools to enhance the execution of discipline policies.